Darwin's backyard : how small experiments led to a big theory - Costa, James T., 1963- (W.W. Norton & Company, 2017)
"James T. Costa takes readers on a journey from Darwin's childhood through his voyage on the HMS Beagle where his ideas on evolution began. We then follow Darwin to Down House, his bustling home of forty years, where he kept porcupine quills at his desk to dissect barnacles, maintained a flock of sixteen pigeon breeds in the dovecote, and cultivated climbing plants in the study, and to Bournemouth, where on one memorable family vacation he fed carnivorous plants in the soup dishes. Using his garden and greenhouse, the surrounding meadows and woodlands, and even taking over the cellar, study, and hallways of his home-turned-field-station, Darwin tested ideas of his landmark theory of evolution with an astonishing array of hands-on experiments that could be done on the fly, without specialized equipment. He engaged naturalists, friends, neighbors, family servants, and even his children, nieces, nephews, and cousins as assistants in these experiments, which involved everything from chasing bees and tempting fish to eat seeds to serenading earthworms. From the experiments' results, he plumbed the laws of nature and evidence for the revolutionary arguments of On the Origin of Species and his other watershed works. Beyond Darwin at work, we accompany him against the backdrop of his enduring marriage, chronic illness, grief at the loss of three children, and joy in scientific revelation. This unique glimpse of Darwin's life introduces us to an enthusiastic correspondent, crowd-sourcer, family man, and, most of all, an incorrigible observer and experimenter."--Jacket flap.